2002
DOI: 10.1002/hyp.282
|View full text |Cite
|
Sign up to set email alerts
|

A classification of drainage and macropore flow in an agricultural catchment

Abstract: Abstract:This paper uses a variety of multivariate statistical techniques in order to improve current understanding of the antecedent and rainfall controls on drainage characteristics for an agricultural underdrained clay site. Using the dataset obtained from a two-year hillslope study at Wytham (Oxfordshire, UK) a number of patterns in the nature and style of drainage events were explored. First, using principal components analysis, a distinction was drawn between drainflow controlled by antecedent conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…For example, Holden and Burt (2002) showed that there was no difference to flowpaths caused by drought when considering results of a bromide tracer experiment, but when considering moisture content an effect could be demonstrated. Therefore, chemical tracers should be considered as one line of evidence and that a study of changes in rainfall-runoff relationships and the event-based hydrology of catchment would be the next line of evidence to consider (Heppell et al, 2002). Secondly, that in such a long-term dataset, as used in this study, the flow pathways being represented are those of average conditions and not just storm runoff conditions.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Holden and Burt (2002) showed that there was no difference to flowpaths caused by drought when considering results of a bromide tracer experiment, but when considering moisture content an effect could be demonstrated. Therefore, chemical tracers should be considered as one line of evidence and that a study of changes in rainfall-runoff relationships and the event-based hydrology of catchment would be the next line of evidence to consider (Heppell et al, 2002). Secondly, that in such a long-term dataset, as used in this study, the flow pathways being represented are those of average conditions and not just storm runoff conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The greater organic matter content in the grassland soils will have reduced the swelling and shrinking (Hillel, 2004) and therefore reduced the likelihood of desiccation crack formation in the grassland soils. Many studies have examined preferential flow down desiccation cracks but most of these studies have been focussed on clay soils (Brown et al, 1999;Heppell et al, 2002) or peat soils (Holden, 2005;Holden et al, 2001) which are more susceptible to shrinkage and swelling and hence more prone to cracking. Field evidence suggested that in the arable sandy loam soils tested, the smaller cracks may have been destroyed by swelling during wetting and some of the larger ones were filled with debris which impeded flow.…”
Section: Discussionmentioning
confidence: 99%
“…In order to analyse the DOC data in terms of the relationship to changes in stream flow, the record was considered as a series of events (see approach by Heppell et al 2002;Worrall et al 2002). The following parameters were tabulated: absolute increase in discharge, absolute decrease or increase in DOC concentration and time between events.…”
Section: Environmental Parametersmentioning
confidence: 99%